2023
DOI: 10.1021/acs.inorgchem.2c04228
|View full text |Cite
|
Sign up to set email alerts
|

Group IIIA Single-Metal Atoms Anchored on Hexagonal Boron Nitride for Selective Adsorption Desulfurization via S–M Bonds

Abstract: Single-atom adsorbents (SAAs) featuring maximized atom utilization and uniform isolated adsorption sites have aroused extensive research interest in recent years as a novel class of adsorption materials research. Nevertheless, it is still challenging to gain a fundamental understanding of the complicated behaviors of SAAs for adsorbing thiophenic compounds (THs). Herein, this work systematically investigated the mechanisms of adsorption desulfurization (ADS) over a single group IIIA metal atom (Ga, In, and Tl)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 80 publications
0
6
0
Order By: Relevance
“…The calculated adsorption energy of 4,6-DMDBT on the VO x /TiO 2 -(101), VO x /TiO 2 -(100), and VO x /TiO 2 -(001) surfaces is 0.67, 0.10, and 0.30 eV, respectively. It has been well-established that too strong or too weak adsorption energies of aromatic sulphides with catalytic active sites on catalyst surfaces are both unfavorable for the AODS process. , Therein, too strong an adsorption energy of aromatic sulfides with catalytic active sites would “poison” the catalyst, while too weak an adsorption energy is unfavorable for the full contact of the reactant with catalytic active sites. Thus, the suitable adsorption energy of 4,6-DMDBT on VO x /TiO 2 -(101) indicates the better activation effect on VO x /TiO 2 -(101) catalysts, which is in accordance with the experimental and AODS results.…”
Section: Resultsmentioning
confidence: 99%
“…The calculated adsorption energy of 4,6-DMDBT on the VO x /TiO 2 -(101), VO x /TiO 2 -(100), and VO x /TiO 2 -(001) surfaces is 0.67, 0.10, and 0.30 eV, respectively. It has been well-established that too strong or too weak adsorption energies of aromatic sulphides with catalytic active sites on catalyst surfaces are both unfavorable for the AODS process. , Therein, too strong an adsorption energy of aromatic sulfides with catalytic active sites would “poison” the catalyst, while too weak an adsorption energy is unfavorable for the full contact of the reactant with catalytic active sites. Thus, the suitable adsorption energy of 4,6-DMDBT on VO x /TiO 2 -(101) indicates the better activation effect on VO x /TiO 2 -(101) catalysts, which is in accordance with the experimental and AODS results.…”
Section: Resultsmentioning
confidence: 99%
“…21−23 However, the aromatic compounds in fuel compete with TS for adsorption on the surface of BNNFs, which pose a huge impact on the selectivity for TS. 21 For ADS application of BNNFs, doping the metal elements onto BNbased materials was reported to be more effective and selective toward eliminating the TS from fuel compared to pristine BN materials. 21,24,25 Recently, our previous theoretical study 21 demonstrated that single-metal atom adsorbents (SAAs), with atomically dispersed group IIIA metal sites, based on boron nitride nanosheets have remarkable adsorption performance for TS through S−M interactions between the sulfur atom in TS and the metal atom in the adsorbent.…”
Section: Introductionmentioning
confidence: 99%
“…21 For ADS application of BNNFs, doping the metal elements onto BNbased materials was reported to be more effective and selective toward eliminating the TS from fuel compared to pristine BN materials. 21,24,25 Recently, our previous theoretical study 21 demonstrated that single-metal atom adsorbents (SAAs), with atomically dispersed group IIIA metal sites, based on boron nitride nanosheets have remarkable adsorption performance for TS through S−M interactions between the sulfur atom in TS and the metal atom in the adsorbent. SAAs are an emerging strategy of adsorbents with atomically dispersed adsorption sites anchored on support materials.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations